2018
DOI: 10.3390/ijerph15091931
|View full text |Cite
|
Sign up to set email alerts
|

The Association between US Adolescents’ Weight Status, Weight Perception, Weight Satisfaction, and Their Physical Activity and Dietary Behaviors

Abstract: Background: It remain unclear that the association between weight status, weight perception, weight satisfaction and the clustering of physical activity (PA) and dietary behaviors in adolescents. Method: A cross-sectional analysis of National Health and Nutrition Examination Survey and the US Department of Agriculture’s Food Patterns Equivalents 2007–2014 data from adolescents aged 12–17 years (n = 2965) was conducted. Multivariable logistic regression models adjusted for demographic characteristics examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 31 publications
(52 reference statements)
5
39
0
Order By: Relevance
“…While increasing evidence highlights that individuals who perceive themselves as too heavy engage in less physical activity and more sedentary behaviours (such as screen time), 21,28–30 these findings offer unique insights into the potential mechanistic role of self‐conscious emotions. Consistent with theoretical tenants 36 and empirical evidence, 39,41 higher levels of shame were associated with less physical activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While increasing evidence highlights that individuals who perceive themselves as too heavy engage in less physical activity and more sedentary behaviours (such as screen time), 21,28–30 these findings offer unique insights into the potential mechanistic role of self‐conscious emotions. Consistent with theoretical tenants 36 and empirical evidence, 39,41 higher levels of shame were associated with less physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…More recent evidence suggests that the probability of males and females perceiving themselves as overweight has declined over time 18 . Additionally, the body image experiences of individuals with overweight or obesity are not homogenous, 19 evidenced by weight underestimations across the lifespan 20–22 . Specifically in young adults, approximately 50% of males and 20% of females with overweight or obesity do not perceive themselves as too heavy 23 .…”
Section: Introductionmentioning
confidence: 99%
“…The association between indexes of diet quality or health behaviors and adiposity in recent scientific literature has been inconsistent. In cross-sectional studies, it has ranged from better diet quality and higher adiposities among children [54], to no significant association [55,56,57] or lack of consistent association [58], to healthier diet patterns in those who were overweight or obese [59]. Other studies only report demographic differences in diet quality in children and not the diet quality–adiposity association [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity during adolescence is associated with many physical and mental health conditions and may have long-term impacts on health status in adulthood [2]. Research has indicated that diet quality, consuming a healthy and balanced diet, may be an important strategy for obesity prevention due to its relationship with overweight or obesity in adolescents [3,4,5]. However, only limited research has examined dietary quality in adolescents [6,7,8], and, to our knowledge, only one study has explored racial/ethnic differences in dietary quality [8].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the purpose of the present study was to systematically explore racial/ethnic and weight-related and physical activity differences in dietary quality and its interactions and independent associations on dietary quality through a progressive set of hypotheses and exploratory analyses using a representative sample of US adolescents and the HEI-2015. Due to the previously identified sex effects [4,8], all analyses were stratified by sex.…”
Section: Introductionmentioning
confidence: 99%